2006
DOI: 10.1111/j.1399-6576.2006.01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of hemodynamic monitoring and vasopressor and inotropic therapy in post‐operative cardiac surgery patients in Germany: results from a postal survey

Abstract: Hemodynamic monitoring and the variability in clinical practice with regard to volume replacement, transfusion triggers and the use of vasopressors/inotropes in cardiac surgery patients tend to follow the results of traditional experience rather than current scientific knowledge. Guidelines are therefore necessary to help to improve the standards of intensive care after cardiac surgery and thus the outcome of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 47 publications
5
86
2
5
Order By: Relevance
“…Undoubtedly, the mean arterial pressure (MAP) is the most mentioned and most commonly used parameter in the treatment of circulatory insufficiency. 40 The Surviving Sepsis Campaign (SCC) Huber (2008) Schmidt (2007) Monnet (2007) Toth (2007) Kozieras (2007) Compton (2007) Kuzkov (2006) Kuhn (2006) Hoffmann (2005) Michelet (2005) Deja (2005) Patroniti (2005) Szakmany (2004) Faybik (2004) Deeren (2004) Sakka (2001) Sakka (2000) Raaijmakers (1998) Zeravik (1990) Figure 7 Forest plot of individual study results and pooled mean estimator from a random-effects meta analysis concerning EVLWI data in non-surgical patients (SEP).…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the mean arterial pressure (MAP) is the most mentioned and most commonly used parameter in the treatment of circulatory insufficiency. 40 The Surviving Sepsis Campaign (SCC) Huber (2008) Schmidt (2007) Monnet (2007) Toth (2007) Kozieras (2007) Compton (2007) Kuzkov (2006) Kuhn (2006) Hoffmann (2005) Michelet (2005) Deja (2005) Patroniti (2005) Szakmany (2004) Faybik (2004) Deeren (2004) Sakka (2001) Sakka (2000) Raaijmakers (1998) Zeravik (1990) Figure 7 Forest plot of individual study results and pooled mean estimator from a random-effects meta analysis concerning EVLWI data in non-surgical patients (SEP).…”
Section: Discussionmentioning
confidence: 99%
“…In cardio-surgical ICU, CVP is the most used (87 % of intensivists), followed by MAP (84 %) and PCWP (30 %) (Kastrup et al 2007). Many studies have shown that CVP does not adequately reflect preload and fails to predict fluid responsiveness (Agrò and Vennari 2013b;Kastrup et al 2007;Cavallaro et al 2008;Marik et al 2008).…”
Section: Hemodynamic Variables In Gdtmentioning
confidence: 98%
“…According to these results, HES is now the preferred colloid in many European countries in the intensive care as well as in the operative setting. Data about the use of HES in Germany were based on postal surveys during 1998 [29] and 2004/5 [34]. In 1998, HES use was reported in 67% of 286 intensive care units [29].…”
Section: Ad 1) Use Of Hes In Actual Clinical Practicementioning
confidence: 99%
“…In the past years, description of volume therapy in acute hypovolemia was derived mainly from self-administered questionnaires [29][30][31][32][33][34][35][36]. According to these results, HES is now the preferred colloid in many European countries in the intensive care as well as in the operative setting.…”
Section: Ad 1) Use Of Hes In Actual Clinical Practicementioning
confidence: 99%